Foreign Professionals and Domestic Regulation - Mattoo, Aaditya; Mishra, Deepak (World Bank, Washington, DC, 2012)
Changes in demographics and patterns of investment in human capital are creating increased scope for international trade in professional services. The scope for mutually beneficial trade is, however, inhibited not only by quotas and discriminatory taxation, but also by domestic regulation - including a range of qualification and licensing requirements and procedures. To illustrate the nature and implications of these regulatory impediments, this paper presents a detailed description of the regulatory requirements faced in the United States market by four types of Indian professionals: doctors, engineers, architects, and accountants. India is one of the largest exporters of skilled services, and the United States is one of the largest importers of skilled services, so these two countries reflect broader global trends. The paper argues that regulatory discrimination, for example through preferential recognition agreements, has implications both for the pattern of trade and for welfare. It presents some illustrative estimates that suggest the economic cost of regulations may be substantial. The paper concludes by examining how the trade-inhibiting impact of regulatory requirements could be addressed through bilateral and multilateral negotiations.